COHESITY OF PRIVATE PRACTICES ON JOURNALISTIC MEDIA IN TANJUNG SELAMAT VILLAGE OFFICE - Sri Wahyuni Sitorus; M. Yoserizal Saragih (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: Tanjung Selamat Village is one of the villages located in Sunggal District, Deli Serdang Regency. Good management of the use of mass media around the village has made this village a positive image from the community. All did not escape the good cooperation between public relations and the mass media. The purpose of this study was to determine the cohesion that was built between village public relations and the mass media. This research includes descriptive qualitative research with an observational approach to find out a complete picture of the cohesiveness of public relations to journalistic media. The subjects of this study amounted to 2 people including the village head of Tanjung Selamat and village public relations. The results of this study are village public relations have established harmonious communication with all mass media around the village in order to increase the effectiveness of the media on the good image of the village, this can be seen from the way the village office is very appreciative and open to the mass media who want to get information. On the other hand, there is great hope for every element of village institutions to continue to improve good communication with the mass media. Keywords: Cohesiveness of Public Relations, Journalistic Media